Lone Star Steeples : Historic Places of Worship in Texas (Book collections on Project MUSE., 2016)
In Lone Star Steeples: Historic Places of Worship in Texas, Carl J. Christensen Jr. and Pixie Christensen present sixty-five captivating and historically significant structures in exquisite watercolor illustrations accompanied by brief summaries and convenient, handcrafted maps. Ranging from stately edifices of brick and stone located in urban centers to more humble wood-frame chapels in rural surroundings, the houses of faith shown in these pages have one important trait in common: They have all served as centers of cultural identity, spiritual comfort, and public service to the communities i.